Efficacy and Safety of Direct-Acting Antivirals in Elderly Patients with Chronic Hepatitis C: A Nationwide Real-Life, Observational, Multicenter Study from Turkey - Onlen, Yusuf; Bal, Tayibe; Cabalak, Mehmet; Oztoprak, Nefise Cuvalci; Sari, Nagehan Didem; Kurtaran, Behice; Tabak, Fehmi (Aves, 2022)
Background: The number and proportion of elderly patients living with chronic hepatitis C are expected to increase in the coming years. We aimed to compare the real-world efficacy and safety of direct-acting antiviral treatment in elderly and younger Turkish adults infected with chronic hepatitis C. Methods: In this multicenter prospective study, 2629 eligible chronic hepatitis C patients treated with direct-acting antivirals between April 2017 and December 2019 from 37 Turkish referral centers were divided into 2 age groups: elderly (>= 65 years) and younger adults (<65 years) and their safety was compared between 2 groups in evaluable population. Then, by matching the 2 age groups for demographics and pretreatment risk factors for a non-sustained virological response, a total of 1516 patients (758 in each group) and 1244 patients (622 in each group) from the modified evaluable population and per-protocol population were included in the efficacy analysis and the efficacy was compared between age groups. Results: The sustained virological response in the chronic hepatitis C patients was not affected by the age and the presence of cirrhosis both in the modified evaluable population and per-protocol population (P =.879, P =.508 for modified evaluable population and P =.058, P =.788 for per-protocol population, respectively). The results of the per-protocol analysis revealed that male gender, patients who had a prior history of hepatocellular carcinoma, patients infected with non-genotype 1 hepatitis C virus, and patients treated with sofosbuvir + ribavirin had a significantly lower sustained virological response 12 rates (P <.001, P =.047, P =.013, and P =.025, respectively). Conclusion: Direct-acting antivirals can be safely used to treat Turkish elderly chronic hepatitis C patients with similar favorable efficacy and safety as that in younger adults.
Keywords: Age; chronic hepatitis C; direct-acting antiviral agents; elderly; Turkey